Temperature and salinity in the Bohai Sea landfast ice: Observations and modelling - Ma, Yuxian; Cheng, Bin; Leppäranta, Matti; Cheng, Yubing; Yuan, Shuai; Xu, Ning; Shi, Wenqi (Elsevier, 2024)
Temperature and salinity are essential thermodynamic properties of sea ice. A 40-day long field campaign was carried out in winter 2020/2021 in the northern Bohai Sea in the landfast sea ice to investigate the seasonal sea ice temperature and salinity evolution. Ice thickness was measured routinely. A thermistor string was used to measure the ice temperature. Ice samples were collected for salinity by coring (Sco) and crumbing (Scr) methods. The mean vertical values of Sco and Scr were 4.8–5.8 psu and 8.3–13.8 psu, respectively. In cold ice, Sco and Scr were very close to each other. When ice temperature increased to − 5 ◦C, Sco and Scr tended to differ from each other, and the difference was at largest at ice bottom. The brine volume fraction (BVF) ranged between 0.03 and 0.21 for Sco and 0.03 and 0.32 for Scr. The growth of ice reached a maximum of 3.7 cm/day in very cold conditions, while the average growth rate was 0.8 cm/day comparable to other seasonally ice-covered seas. A numerical sea ice thermodynamic model was applied to simulate the ice thickness with particular attention to the effect of Sco and Scr on the ice mass balance. The modeled overall ice growth rate was 0.7 cm/day and agreed well with the observations but during cold periods the simulation was biased down (1.1 cm/day); a possible reason is underestimation of the thermal conductivity in the model. The modeled ice thickness differed by 3 cm when using Sco and Scr as the input salinity profiles indicating that salinity has a minor impact on sea ice mass balance during mid-winter.